A COMPARATIVE STUDY ON THE IMPLEMENTATION OF DEFENDS AND PLEASE STRATEGIES TOWARD STUDENTS WRITING COMPETENCY IN SMP N 2 SINGARAJA - ., Ni Luh Karisma Dewi; ., Dra. Luh Putu Artini, MA., Ph.D.; ., Kadek Sonia Piscayanti, S.Pd., M.Pd. (Universitas Pendidikan Ganesha, 2017)
Penelitian ini adalah penelitian eksperimen yang menginvestigasi perbedaan signifikan dalam kompetensi menulis siswa dengan membandingkan kelas dengan strategi DEFENDS dan kelas dengan strategi PLEASE. Untuk bisa menjalankan penelitian ini, siswa kelas 7 di SMPN 2 Singaraja dipilih untuk digunakan sebagai sample. 2 kelas diberikan perlakuan yang berbeda dengan mengimplementasikan DEFENDS and PLEASE strategy. Pre Test dan Post Test Non Group Design diimplementasikan dalam penelitian ini. Data mengenai kompetensi menulis siswa dikumpulkan melalui post test. Penelitian ini menunjukkan bahwa terdapat perbedaan yang signifikan dalam hal kompetensi mengajar antara murid yang diajar dengan strategi DEFENDS dan kelas yang diajar dengan strategi PLEASE. Ini dapat dilihat dari Sig (2-tailed) yang dibawah 0.05 yang berarti kompetensi menulis siswa dengan strategi DEFENDS (76.35) lebih tinggi dari strategi PLEASE (70.27). Hasil penelitian ini menunjukkan bahwa strategi DEFENDS lebih efektif digunakan dalam mengajar menulis, kususnya dalam menulis teks deskripsi. Kata Kunci : Strategi DEFENDS, Strategy PLEASE, Kemampuan Menulis This study was an experimental study investigated the significant difference in writing competency between the students taught by using DEFENDS and PLEASE strategies. To conduct this research the seventh grade students of SMP N 2 Singaraja in the academic year 2017/2018 were selected to be sample. Two classes were treated differently by implementing DEFENDS and PLEASE strategies. Pre Test-Post Test Non Control Group Design was implemented in this experiment. The data of students’ writing competency were collected by using post test. This research discovers that there is a significant difference in writing competency between the students’ taught by using DEFENDS strategy and those taught by PLEASE strategy. It is known from the probability value or Sig.(2-tailed) of 0.000 which is lower than 0.05. The mean score of the students writing competency taught by DEFENDS strategy (76.35) was higher than the mean score of the students writing competency (taught by using PLEASE strategy (70.27). This finding demonstrating that DEFENDS strategy is more effective for teaching writing, especially in the content of descriptive text.keyword : DEFENDS Strategy, PLEASE Strategy, Writing Competency